Isu Pendidikan Islam Di Era Global - Difa’ul Fikri Jayyid; Sukari (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the concepts, challenges, impacts, and opportunities regarding Islamic education in the global era. Employing a qualitative approach via library research, data were gathered through the documentation of literature sources and analyzed using an interactive model. The findings indicate that the concept of Islamic education must integrate spiritual values with the demands of modernity. Key challenges include adolescent identity crises, educators' limited digital competence, and the requirements for 21st-century skills. Although it has triggered commercialization and cultural erosion, globalization has also had positive impacts, such as expanded access to knowledge and innovations in digital learning methods. In conclusion, globalization presents strategic opportunities for the integration of contemporary knowledge, techno-pedagogical digitalization, and the reconstruction of a